2000
DOI: 10.1046/j.1365-8711.2000.03127.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly oscillating M giant stars?

Abstract: The Hipparcos mission discovered a few dozen M giant stars with periods P shorter than 10 d. Similar stars may be found in other large data bases of new variables (e.g., OGLE). The three possible sources of the magnitude variations – pulsation, starspots and ellipsoidal deformation – are discussed in general terms. The parallaxes and V−I colour indices are used to calculate radii and temperatures for all M giant variables with P<100 d. Masses are estimated from the positions of the stars in a Hertzsprung–Russe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 27 publications
2
57
1
Order By: Relevance
“…As stated above, the results of Koen & Laney (2000) support the presence of rapid oscillations in M-giants derived from Hipparcos photometry. For the only star in common with us, RV Cam, we already showed that no comparable short period is present in our APT material.…”
Section: Rapid Oscillations?supporting
confidence: 80%
See 2 more Smart Citations
“…As stated above, the results of Koen & Laney (2000) support the presence of rapid oscillations in M-giants derived from Hipparcos photometry. For the only star in common with us, RV Cam, we already showed that no comparable short period is present in our APT material.…”
Section: Rapid Oscillations?supporting
confidence: 80%
“…It even should easily allow the detection of rapid variations (<10 days!) proposed recently by Koen & Laney (2000) for some M-giants having Hipparcos photometry (see below). Table 1 gives an overview of the resulting time scales.…”
Section: Period Findingmentioning
confidence: 84%
See 1 more Smart Citation
“…While Φ for the 9 period fit is slightly higher, we have to compensate for the fact that we have added an extra period. Reduced χ 2 's and the Bayes information criterion (BIC, Koen & Laney 2000) both indicate that the two fits are equivalent in quality. Occam's razor favors the 9 period fit (no need for a magnetic field in that case).…”
Section: Asteroseismological Fitsmentioning
confidence: 99%
“…The authors thank the anonymous referee for the constructive comments and recommendations on the manuscript. We thank Gerald Handler for providing the KUV 05134+2605 data obtained in 1988 , 1992, 2000 October, 2001, and during the Whole Earth Telescope campaign in 2000 (XCov20). The authors also acknowledge the contribution of L. Molnár, E. Plachy, H. Ollé and E. Verebélyi to the observations of KUV 05134+2605.…”
mentioning
confidence: 99%